Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units